Effect of Examination Stress on Brain Oscillations During Memory Tasks in Human Females During the Luteal Phase - Yousof, Shimaa Mohammad; El-Baz, Amani; Ibrahim, Dalia; Osama, Ahmed; El-wazir, Yasser (PSM Biological Research, 2019)
Stress is known to increase the activity of the hypothalamic adrenal axis. Some researchers were unable to find an effect of stress on memory retrieval in females. A quantitative electroencephalogram (qEEG) provides an objective assessment of the electrical activity of the brain via many techniques such as power spectral analysis and coherence. The current study was conducted to assess the effect of examination stress on qEEG oscillations during delayed memory retrieval in females during the luteal phase. A Prospective longitudinal study was applied to 11 healthy females. qEEG analysis was done using the relative power (RP) and the peak power frequency (PPF) during memory tasks. Serum cortisol was analyzed as a measure of stress. Serum estrogen and progesterone were assessed to validate the phase of the menstrual cycle. All hormonal analyses were done by enzyme-linked immunosorbent assay (ELISA) technique. The results revealed insignificant effects on the quantitative analysis of EEG oscillations during the luteal phase regarding the mean relative power in all frequency bands (delta "?"; P-value: 0.38 and 0.41, theta "?"; P-value: 0.26 and 0.87, alpha "?"; P-value: 0.69 and 0.85 and beta "?"; P-value: 0.91 and 0.74 during the word and photo recognition tasks; respectively). Regarding the peak power frequency EEG analysis; there were no significant differences in (?, ?, ?, and ?) EEG bands during the word and photo- recognition tasks over the central (C3 and C4) and occipital (O1 and O2) sites in stress compared to non-stress periods; P- values were: C3: 0.37 and 0.55, C4: 0.33 and 0.11, and were: O1: 0.13 and 0.13 and O2: 0.9 and 0.29 during the word and photo recognition memory tasks; respectively. It is concluded that gonadal steroids have no effect on brain oscillation during both resting and stress conditions.